SEMANTIC FUNCTION OF ANTHROPONYMS USED IN O‘TKIR HOSHIMOV’S SHORT STORY ODAM OVOZI - S.B.Khursankulov,; D.Z.Abduazimova, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  This  article  analyzes  the  linguopoetic  and  semantic  features  of anthroponyms used in the short story “The Voice of Man” by  O‘tkir Hoshimov. It substantiates  that  the  names  occurring  in  the  story, such  as  Mastura,  Yo‘ldoshali, Asqarjon,  Lola,  and  Zamira,  function  not  only  as  nominative  units  but  also  as important  artistic  and  aesthetic  devices.  Furthermore,  the  study  examines  how anthroponyms  contribute  to  the  representation  of  social  issues,  particularly  the relationships between parents and children, on a scientific basis. As a result of the research,  the  functional  significance  of  anthroponyms  in  enhancing  the  overall linguopoetic expressiveness of the text is identified.